Load test of pre-cast geopolymer concrete slabs - C. Ridtirud; V. Lam; C. Sapsin (International Association of Lowland Technology, 2018)
This research aims to study load testing of pre-cast geopolyme r concrete slab. Fly ash, a by-product of generation process of electricity was used in mixture as alternative to ordinary Portland cements in this research. To design and produce pre-cast geopolymer concrete slab, the compressive strength of geopolymer concrete was tested by using fly ash: fine aggregate: coarse aggregate ratio of 1:0.95:1.76 by weight, and the ratio of sodium silicate to sodium hydroxide of 1:1 by weight. The pre-cast geopolymer concrete slab of 0.35x2.40x0.05 m. was designed with live load of 150 kg/ sq. m, five PC-wire of 4 mm. with ultimate strength not less than 17,500 kg/ sq. cm, and was pulled by forced of 13,329 kg/ sq. cm. In this research, precast geopolymer concrete slab was casted and tested by following to Thai Industrial Standards Institute 577-2531. The result of testing pre-cast geopolymer concrete slab was showed that, the value of deflection was exceeded and rebound was less than allowable by the Thai Industrial Standards Institute 577-2531. However, in this research the pre-cast geopolymer concrete slab might be stronger and increase load bearing capacity if the processing of temperature was raised.